Standards of validity and reliability in quantitative and qualitative research: Methods of application - Dahmani, Souhaila (The International tax journal, 2026)
The data collection stage is widely recognized as one of the most challenging phases in scientific research. It requires the researcher to select an appropriate instrument capable of gathering the maximum amount of information necessary to achieve meaningful and generalizable results. When designing this instrument, it is imperative that the researcher conducts preliminary trials and applies established standards of validity and reliability. Such a process ensures that the data collection tools are truly valid and that the results produced are reliable. Any shortcomings in the instrument’s validity or reliability directly compromise the accuracy and overall integrity of the study’s findings, thereby diminishing the research’s value and rendering it a waste of time, effort, and resources for both the researcher and its beneficiaries.